Characteristics of Pore Volume Distribution and Methane Adsorption on Shales - Rui Wang; Ningsheng Zhang; Xiaojuan Liu; Xinmin Wu; Jie Chen; Lijing Ma (Adsorption Science & Technology)
Shale pore structure has an important effect upon shale-gas adsorption. In order to quantify their contribution to the total amount of adsorbed gas, we investigate the pore volume distribution on shale, coal, isolated kerogen, and clay samples using low pressure nitrogen and carbon dioxide adsorption method. And a series of methane adsorption isotherms on the samples was measured by a volumetric approach at 20 °C, 30 °C and 40 °C under pressures up to 10 MPa. Results indicate that a strong correlation exists between TOC and micropore volume of shale, but to verify the correlations between BET surface area and TOC, or micropore volume and Ro are still difficult. Certain isotherms on shales differ from Type I IUPAC (International Union of Pure and Applied Chemistry) isotherm. The unusual shape may be attributed to shale pore structure or composition. Finally, the modified D-A-Langmuir model including pore distribution parameters can provide a precise representation of the methane adsorption data on shales. The findings of this study are applicable to the accurate resource assessments and recovery technologies for shale-gas.